A benchmark of measurement approaches to track the natural evolution of spall severity in rolling element bearings. (1st March 2022) - Zhang, Hengcheng; Borghesani, Pietro; Randall, Robert B.; Peng, Zhongxiao
Highlights: The evolving spall sizes were measured during run-to-failure experiments for REBs. Four measurements (acceleration, AE, IAS, and displacement) were compared. Displacement was the best for spall size estimation, and acceleration comes next. IAS correlates well with spall size, albeit not a direct quantitative size. AE was found poor in both quantification and tracking of natural spall size. Abstract: Bearing prognostics is an important aspect in condition-based maintenance (CBM), and a key step to successful prognostic methods is the ability to quantify the fault severity of the bearing. Previous studies have resulted in some severity assessment methods based on certain types of signals, such as vibration, acoustic emission (AE) and instantaneous angular speed (IAS), however, their performances were not compared, especially in terms of their ability to track the severity of naturally growing spalls. In this paper, four measurement approaches were tested on the same rig for bearing run-to-failure experiments, and their signals were analysed individually and compared. It was found that IAS and radial load (a proxy for displacement) required less processing to provide a reliable assessment of bearing fault severity, acceleration required sophisticated techniques to extract spall-size estimates, whereas AE could not track fault evolution accurately.